Viabilitas Azotobacter spp. pada Beberapa Kombinasi Media Pembawa - SONIARI, NI NENGAH; SUTARI, NI WAYAN SRI (Agrotrop : Journal on Agriculture Science; Vol 12 No 1 (2022)DO - 10.24843/AJoAS.2022.v12.i01.p07, 2022)
Azotobacter spp . Viabilities on Some Combinations of Carrier Media . The purpose of this research was to find suitable carrier media for the survival of Azotobacter spp. as a biological fertilizer, before being applied to the field. The method used in this research is explorative, by inoculating Azotobacter spp. Isolate on 4 types of carrier media, namely soil; cocopeat; wood dust and charcoal with a combination of the following: K1 (Land); K2 (soil + cocopeat); K3 (Soil + sawdust) and K4 (Soil + husk charcoal), which were repeated 3 times, so there were 12 experimental units. Analysis of N, P, K, C-organic and pH for soil media, while for cocopeat, wood powder and husk charcoal, an analysis of N and P, C-organic tissue and pH was carried out. The parameters observed were optical density at 2, 4, 6 and 8 weeks. The results showed that the survival of Azotobacter spp. in K4 carrier media (a combination of soil and husk charcoal) is more secure than other types of carrier media with optical density that has not decreased. Analysis of N and P for rice husk charcoal tissue gave the highest results, namely 1,680% and 1,351%, which were one of the supporters of this inoculant viability. Azotobacter spp. viability still guaranteed until 6 weeks incubation period, in several media, (soil + cocopeat), (soil + sawdust), and (soil + husk charcoal). The combination of media (soil + husk charcoal) gave the highest population increase at the 6 weeks incubation period.